Recovery Assessment Scale‐Domains and Stages: Measurement capacity, relevance, acceptability and feasibility of use with young people. Issue 2 (5th July 2019) - Hancock, Nicola; Scanlan, Justin N.; Kightley, Michelle; Harris, Anthony
Abstract: Aim: The Recovery Assessment Scale‐Domains and Stages (RAS‐DS) is a self‐rated measure of mental health recovery. While this instrument has demonstrated good measurement properties and acceptability to clinicians and consumers in adult mental health services, it has not been evaluated in the context of youth‐focused mental health services. This study was established to evaluate the measurement properties, feasibility and acceptability of the RAS‐DS in a youth mental health service context. Methods: Young people accessing a youth mental health service were invited to complete the RAS‐DS and both young people and clinicians provided feedback about its usefulness. Analyses of the measurement properties of the RAS‐DS were completed using Rasch analysis. Usability feedback was analysed using descriptive statistics and constant comparative analysis. Results: Fifty‐eight consumer‐clinician dyads participated. Analyses revealed that items on the RAS‐DS generally demonstrated good fit with the expectations of the Rasch model and clinician and consumer feedback was generally positive. Ninety‐one percent of young people completed the RAS‐DS in less than 15 minutes. Thirty‐four percent of young people had measure scores above the level of the "hardest" item on the RAS‐DS, suggesting that measurement precision is lower for individuals at more advanced stages of recovery. Conclusions: This study demonstrates that the RAS‐DS has acceptable measurement properties and was acceptable to young people and clinicians. Future research should explore the use of the RAS‐DS by young people in other contexts as well as explore whether additional items could be added to capture the later stages of recovery for young people.